Software development for sensor integration with TV whitespace based chipset - Pushkarna, Rajat (Nanyang Technological University, 2021)
The work presented here focuses on developing software for sensor integration of a TV whitespace-based chipset for IoT applications. The major advantage of such a device is that it utilizes the unlicensed spectrum of TV band thereby it is also a source of free WiFi. TVWS can be used for low data rate applications like, security alarms or IoT network sensor data. TV whitespace is a key enabler for IoT in remote location owing to its large coverage, penetration and cost-effectiveness. A major part of this work focuses on developing WN17 which is a TVWS based chipset for easier sensor integration. Software codes for integration protocols like ADC, UART, SPI, PWM and I2C have been developed for making sensor integration easier. The device has the capability to operate in the frequency range of 470-530MHz, therefore software based dynamic frequency selection is also carried out to easily switch to any frequency between the specified range. To determine the quality of the wireless link, the software has been provided the capability to check received signal strength. During the development of the firmware as part of the work various other parameters are also utilized to enhance the performance of the device using the in-built features. The codes are developed using C programming language and are compiled using Keil IDE for A9159 chipset developed by Amicomm. The compiler tools are proprietary to Amicomm and cannot be copied in any form. WN17 supports TinyOS which is an 8051 micro-controller. In the work four tasks are used in sequence as part of the threads an operating system can support. The firmware for WN17 includes various predefined parameters which cannot be altered during the integration of the device as a sensor network. The modulation scheme used in WN17 is FSK/GFSK based trans-receiver. Direct Spread Spectrum (DSSS) is also used to enhance the spectral bandwidth which can be enabled or disabled using the software code. The IC is provided with multiple operational mode for various power modes, variable Tx power mode making it suitable for power crunch scenarios.